472 A PILOT COLORECTAL AND GERIATRIC MEDICINE (CGM) CLINIC FOR OLDER, FRAIL PATIENTS REFERRED VIA A 2 WEEK WAIT PATHWAY. (14th June 2021) - Thomas, M; Cookson, K; Clark, R; Pearce, L; Fox, J; Price, A
Abstract: Introduction: The two week wait (2ww) colorectal referral pathway was introduced to expedite referrals where cancer is suspected, facilitating prompt diagnosis +/− intervention. Older frail patients are referred via this 2ww pathway even when invasive testing and intervention may not be appropriate. These patients may benefit more from holistic assessment than a universally surgical approach. A Colorectal and Geriatric Medicine (CGM) 2ww referral clinic was piloted, delivered by an urgent referral colorectal specialist nurse and an advanced clinical practitioner in geriatric medicine. Method: Patients >65 years with a Clinical Frailty Scale (CFS) score of 5 or more at referral were directed to the CGM clinic. A telephone consultation was undertaken, incorporating both 2ww assessment and aspects of comprehensive geriatric assessment. Results: 42-patients were reviewed in the clinic. Mean age was 86.1 years and mean CFS 6. 12-patients underwent CT, and 2 CT virtual colonoscopy. No patients underwent endoscopic investigation and 28-patients declined any investigation. Of those who underwent investigation, no cancers were identified. 1 patient was referred on for endosocpic mucosal resection of polyps. 5-patients had severe diverticular disease, which accounted for their symptoms. Medication recommendations were made for 30-patients, some of which led to symptom cessation. Onward referrals were made to a community geriatrician, diabetes and continence teams, and palliative care specialists. 9-patients were identified as meeting criteria for advance care planning. This was commenced during the consultation and communicated back to the referring clinician for further action. Conclusion: Older, frail patients are often not able, nor wish to undergo, invasive investigations but should not be disadvantaged or delayed in their pathway. Further work is needed to determine the most appropriate referral pathway for this group of patients. Holistic assessment that leads to improvement in symptoms and future planning may not be achievable through a solely surgical assessment.